Efectos altitudinales en la africanización de las colonias de abejas melíferas (Apis mellifera L.) en Jalisco, México - Contreras-, Francisca; Ramos-Cuellar, Ana Karen; De la Mora, Alvaro; Morfin, Nuria; Tapia-González, José M.; Macías-Macías, Jose O.; Petukhova, Tatiana; Correa-Benítez, Adriana; Guzman-Novoa, Ernesto (Ecosistemas y Recursos Agropecuarios, 2023)
This study determined the African or European ancestry of honey bee colonies in six regions of Jalisco, using morphometric and mitochondrial DNA indicators. More than 50% of the colonies in Jalisco had African mitotype and morphotype (59.0% and 62.5%, respectively). The frequency of africanization of the studied colonies was significantly higher (p< 0.05) in regions of low altitude and in subtropical climates, such as the Southeast and Southwest regions, than in regions of higher elevation and in temperate climates, such as Los Altos